The Process and Implication of Inter-Professional Education: A Systematic Review - Prabawati, Dewi (Department of Nursing, Faculty of Medicine, Diponegoro University, 2017)
Background: The practice of inter-professional education (IPE) is expanding rapidly especially in the developing countries. The goal of IPE is to develop knowledge, skills, and attitudes that result in effective Inter-professional (IP) team behaviors and competency. Therefore, it is essential to understand more about the activity, other professional’s involvement and its implications for nursing students and institutions.Purpose: This paper aimed to review the process and other professional’s involvement in IPE’s nursing education, and describe the implication after implementing IPE for nursing students and institution.Methods: A comprehensive multi-step search of the literature in IPE using ProQuest, EBSCO and Cengage databases was performed. Samples of 19 studies met the inclusion criteria and were used in this study.Results: None of the studies reported findings from developing country, while there were only two studies conducted in Asia. IPE programs utilize a variety of combinations of interactive learning methods, such as group problem solving, focus group interview, social networking (website), and simulated patient or simulated based training (SBT) which is becoming the most common methods employed. IPE gives benefits for the students, such as improving communication skills, recognizing the role and responsibilities, understanding the value and ethics and also increasing teamwork and team-based care.Conclusion: Despite the limitations, this systematic review found a number of activities and other professionals that can be involved with nursing in the IPE implementation. It also found out that IPE applied in a variety of clinical settings is well received by the students and enable them to learn the knowledge and skills for collaborative learning.